Nicotinamida e fitohormônios como bioestimulantes na cultura do milho - Silvia Elena Navarrete Thomé (2021)
Brazil has three corn crops, the first two of which are more expressive: summer crop (first crop) and the dry crop (second crop). For the increase in corn productivity, some techniques such as the application of bioestimulants that act in cell differentiation, division and elongation, allowing greater tolerance of plants to biotic and abiotic stresses, improving the development and growth of the root system and consequently the aerial part. The use of vitamins relieves stress and improves physiological characteristics, favoring the metabolism of the plant, also allowing for plant development and growth. The associated use of nicotinamide with phytohormones was beneficial for the characteristics of mass of grains per plant, mass of a thousand grains and productivity of corn grains. The interaction of nicotinamide and phytohormones was able to promote gains for the variables plant height, ear insertion height, ear diameter and thousand grains mass. The highest productivity of corn grains in the first and second harvest was achieved with the concentration 800 mg L-1 of nicotinamide in the presence of the phytohormone Stimulate®. The objective of the work was to evaluate the effect of the application of nicotinamide and phytohormone, leaf path, on growth characteristics, production components and productivity of first and second crop corn grains. The experimental design was in randomized blocks, in 2x5 factorial scheme, with the presence and absence of the phytohormone Stimulate® (cytokinin 0,09 g L-1 + gibberellic acid 0,05 g L-1 + 4-indole-3-ylbutyric acid 0,05 g L-1) in the dosage of 500 mL ha-1 and five concentrations of nicotinamide (0, 200, 400, 600 and 800 mg L-1 ), with four replications. Growth characteristics, ears, production componentes and productivity of first and second crop corn were evaluated. The application of nicotinamide and phytohormone increased the productivity of corn first and second crop conveniente for use in corn culture.